x=3y+13

Rewrite the equation as 3y+13=x.

3y+13=x

Subtract 13 from both sides of the equation.

3y=x-13

Divide each term in 3y=x-13 by 3.

3y3=x3+-133

Cancel the common factor of 3.

Cancel the common factor.

3y3=x3+-133

Divide y by 1.

y=x3+-133

y=x3+-133

Move the negative in front of the fraction.

y=x3-133

y=x3-133

The given equation y=x3-133 can not be written as y=kx2, so y doesn’t vary directly with x2.

y doesn’t vary directly with x

Find the Quadratic Constant of Variation x=3y+13